2015
DOI: 10.1007/s10071-015-0889-6
|View full text |Cite
|
Sign up to set email alerts
|

Learned vocal and breathing behavior in an enculturated gorilla

Abstract: We describe the repertoire of learned vocal and breathing-related behaviors (VBBs) performed by the enculturated gorilla Koko. We examined a large video corpus of Koko and observed 439 VBBs spread across 161 bouts. Our analysis shows that Koko exercises voluntary control over the performance of nine distinctive VBBs, which involve variable coordination of her breathing, larynx, and supralaryngeal articulators like the tongue and lips. Each of these behaviors is performed in the context of particular manual act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…Primates' vocalisations and human speech present homologies in terms of articulation and acoustics by production and use of proto‐vowels (through typical, ‘voiced’ calls/vocalisations such as grunts and barks, resulting from the activation of their vocal folds and their regular oscillation) and proto‐consonants (through atypical, ‘voiceless’ calls such as lip‐smacks and raspberries, resulting from supra‐laryngeal manoeuvring) either singly or in relatively simple syllable‐like call combinations (Lameira, , ; Lameira, Maddieson & Zuberbuhler, ; Lameira et al ., , ; Boë et al ., ; Bergman et al ., ). Growing data report consonant‐like signal types emitted by great apes [bonobos (Taglialatela, Savage‐Rumbaugh & Baker, ); chimpanzees (Hopkins, Taglialatela & Leavens, ; Taglialatela et al ., ; Watts, ); gorillas (Lameira, Maddieson & Zuberbuhler, ; Perlman & Clark, ; Robbins et al ., ); orangutans (e.g. van Schaik et al ., ; Hardus et al ., ; Wich et al ., )] and various monkey species [e.g.…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%
“…Primates' vocalisations and human speech present homologies in terms of articulation and acoustics by production and use of proto‐vowels (through typical, ‘voiced’ calls/vocalisations such as grunts and barks, resulting from the activation of their vocal folds and their regular oscillation) and proto‐consonants (through atypical, ‘voiceless’ calls such as lip‐smacks and raspberries, resulting from supra‐laryngeal manoeuvring) either singly or in relatively simple syllable‐like call combinations (Lameira, , ; Lameira, Maddieson & Zuberbuhler, ; Lameira et al ., , ; Boë et al ., ; Bergman et al ., ). Growing data report consonant‐like signal types emitted by great apes [bonobos (Taglialatela, Savage‐Rumbaugh & Baker, ); chimpanzees (Hopkins, Taglialatela & Leavens, ; Taglialatela et al ., ; Watts, ); gorillas (Lameira, Maddieson & Zuberbuhler, ; Perlman & Clark, ; Robbins et al ., ); orangutans (e.g. van Schaik et al ., ; Hardus et al ., ; Wich et al ., )] and various monkey species [e.g.…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%
“…However, there is clear evidence for a cultural spread across a group in the chimpanzee case . Finally, the enculturated gorilla Koko shows clear voluntary control over her breathing, making a variety of huffs, lip buzzes, and even playing the harmonica . What makes these apparent exceptions interesting is that none involves control of phonation, but rather of the jaws, lips, and tongue (and some respiratory control)—a fact that will become crucial below when we consider mechanistic hypotheses about the neural basis of vocal learning.…”
Section: Vocal Learning As a Key Innovation For Speechmentioning
confidence: 99%
“…Accordingly, behavioral studies of monkeys reported of ability to modify contact calls with intonations (Biben et al, 1986;Sugiura, 1998) or of learning to use them in order to request objects (Hihara et al, 2003). Anecdotal reports of more generalized volitional vocal control, albeit rudimentary, were also reported in apes (Hayes & Hayes, 1952;Hopkins et al, 2007;Koda et al, 2007;Koda et al, 2012;Lameira et al, 2015;Laporte & Zuberbühler, 2010;Perlman & Clark, 2015;Taglialatela et al, 2003;Wich et al, 2008).…”
Section: The Role Of the Ads With The Detection Of Contact Callsmentioning
confidence: 98%